Akt isoforms in the immune system - Guerau-de-Arellano, Mireia; Piedra-Quintero, Zayda L.; Tsichlis, Philip N. (Frontiers in Immunology, 2022)
Akt is a PI3K-activated serine-threonine kinase that exists in three distinct isoforms. Akt’s expression in most immune cells, either at baseline or upon activation, reflects its importance in the immune system. While Akt is most highly expressed in innate immune cells, it plays crucial roles in both innate and adaptive immune cell development and/or effector functions. In this review, we explore what’s known about the role of Akt in innate and adaptive immune cells. Wherever possible, we discuss the overlapping and distinct role of the three Akt isoforms, namely Akt1, Akt2, and Akt3, in immune cells.